The 10th EAA International Symposium on Hydroacoustics - on Hydroacoustics, The 10th EAA International Symposium (Archives of Acoustics, 2016)
The 10th EAA International Symposium on Hydroacoustics, which is also the 33rd Symposium on Hydroacoustics in memory of Prof. Leif Børnø organized in Poland, will take place from May 17 to 20, 2016, in Jastrzębia Góra. It will be a forum for researchers, who are developing hydroacoustics and related issues. The Symposium is organized by the Gdańsk University of Technology and the Polish Naval Academy. The Scientific Committee comprises of the world – class experts in this field, coming from, among others, Germany, UK, USA, Taiwan, Norway, Greece, Russia, Turkey and Poland. The chairman of Scientific Committee is Prof. Eugeniusz Kozaczka, who is the President of Committee on Acoustics Polish Academy of Sciences and Chairman of Technical Committee Hydroacoustics of European Acoustics Association.